THE EFFECT OF INTEREST RATE, INFLATION, EXCHANGE RATE, GROSS DOMESTIC PRODUCT, DOW JONES INDEX AND COVID-19 ON COMPOSITE STOCK PRICE INDEX IN INDONESIA STOCK EXCHANGE PERIOD OF 2015-2020 - Ratnaningrum anstratna@gmail.com; Hutapea, Ganda T.; Malau , Melinda (Universitas Kristen Indonesia, 2022)
This study aims to determine the effect of BI interest rates, inflation, Rupiah exchange rate against US dollar, GDP growth, Dow Jones Index and Covid-19 as Dummy variable on the composite stock price index during the 2015-2020 period. Data analysis with SPSS using descriptive statistics, classical assumption, multiple linear regression test and hypothesis test using t-test, F-test, and determination of R2. The results showed that BI interest rates and inflation have no effect on the composite stock price index. Rupiah exchange rate against the US dollar have a negative and significant effect on the composite stock price index. GDP growth and Dow Jones Index have a positive and significant effect on composite stock price index. Covid-19 as a dummy variable significantly affecting composite stock price index during the 2015-2020 period.Keywords : Composite Stock Price Index, Interest Rates, Inflation, Exchange Rate, Gross Domestic Product (GDP), Dow Jones Index, Dummy Covid-19